Upgrading of waste stabilization ponds using a low-cost small-scale fine bubble diffused aeration system - Ramazan Vagheei (IWA Publishing, 2021)
Waste Stabilization Ponds (WSPs) are known for the economical treatment of wastewater, especially if low-cost land is available. In this research to overcome some common operational problems such as undesirable color changes in ponds, severe odor problems, and most importantly, deviations from the effluent standards, the performance of a novel installation of a small-scale fine bubble diffused aeration system in the inlet zone of the facultative pond has been investigated. The long-term operational data of the system in two wastewater treatment plants in the east of Iran demonstrated that this system can significantly improve the efficiency of the treatment plant in addition to eliminating the mentioned operational problems. Pre-aeration of the inlet zone of the facultative ponds (Birjand WSPs) by the aeration system consists of 250 fine bubble disk diffusers (12 inches in diameter) and one 22 kW roots blower showed that purple color and odor problem can eliminate after almost two weeks and organic matter removal efficiency increased from 58 ± 15% to about 85 ± 10% based on BOD5. Almost similar results were obtained from the WSPs of Neyshabur. Long-term experimental results showed this system can be used successfully to control the process and upgrade these natural and efficient treatment processes, especially in developing countries. HIGHLIGHTS Low cost and efficient upgrading option for waste stabilization ponds.; Design an auxiliary control system for waste stabilization ponds.; Assessment of using a small-scale fine bubble diffused aeration system on performance of waste stabilization ponds.;